2016
DOI: 10.18632/oncotarget.13965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipopolysaccharide on maturation of bovine oocyte in vitro and its possible mechanisms

Abstract: Lipopolysaccharide disturbs the secretion of gonadotropin, endometrial function and implantation efficiency. However, there is little information regarding the effects of lipopolysaccharide on cyclic ovary activity, especially oocyte maturation. Therefore, we aimed to investigate the effects of lipopolysaccharide on the maturation potential of bovine oocytes. We found that lipopolysaccharide exposure significantly decreased the first polar body extrusion rate and delayed the cell cycle progression. The abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…Previous data suggest that exposure of COCs to either LPS or TNF‐α reduces progression to the blastocyst stage of development by 16 or 8 percentage points, respectively (Soto et al, ). Our work here and by others have demonstrated alterations in the machinery and status of the epigenome of the oocyte following exposure to LPS (Zhao et al, ). We hope that future experimentation will be able to evaluate the epigenetics and phenotype of cattle conceived following oocyte exposures.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous data suggest that exposure of COCs to either LPS or TNF‐α reduces progression to the blastocyst stage of development by 16 or 8 percentage points, respectively (Soto et al, ). Our work here and by others have demonstrated alterations in the machinery and status of the epigenome of the oocyte following exposure to LPS (Zhao et al, ). We hope that future experimentation will be able to evaluate the epigenetics and phenotype of cattle conceived following oocyte exposures.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, we observed an LPS‐mediated increase in transcript abundance of the histone deacetylase HDAC1 , suggesting possible dysregulation of histone posttranslational modifications. Interestingly, it has been reported that oocytes matured in the presence of LPS have reduced DNA methylation (5‐mC) and histone H3 lysine 9 dimethylation (H3K9me2), whereas histone H3 lysine 4 dimethylation (H3K4me2) is increased (Zhao et al, ). It is interesting to postulate if the altered transcripts involved in epigenetic programing observed here may affect enduring epigenetic marks that could affect the phenotype of subsequent offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active states of lipopolysaccharide, tumor necrosis factor (TNF), and phorbol myristate acetate (PMA) were predicted in the aged oocytes based on the expression changes of their downstream genes in our dataset (Additional file 1: Figure S2). Exposure to lipopolysaccharide was reported to inhibit the maturation potential of bovine oocytes by affecting cell cycle, cytoskeletal dynamics, oxidative stress, and epigenetic modifications [20]. In porcine and cattle, TNF could inhibit the maturation of oocytes from GV to MII stage and increase the proportion of oocytes with abnormal chromosome alignment and cytoskeleton structure [21,22].…”
Section: Decoding Transcriptional Dynamics During Oocyte Agingmentioning
confidence: 99%
“…At the mitosis stage, gene expression could be propagated by the histone acetylation, the level of H3K4me2 was increased, but the DNA methylation (5-mC) and H3K9me2 were decreased (Zhao et al, 2017), while the misexpression could be caused by the aberrant H3K4me3 and H3K27me3 (Xu et al, 2017). If the discharge of the PB1 is suppressed, the level of H3K4me2 will increase, while the level of 5mC and H3K9me2 will decrease (Zhao et al, 2017).…”
Section: Figmentioning
confidence: 99%